Analisis Pengendalian Kualitas Produk Jok Dengan Metode Seven Tools Untuk Mengurangi Kecacatan Produk Di PT ABC - Candra Kusuma, Gopala; Izzhati, Dwi Nurul (Universitas Kadiri, 2026)
The high number of defective seat products in PT. ABC’s production process indicates quality control issues that require systematic analysis. This study aims to evaluate whether the production process remains within acceptable control limits and to identify the types and causes of product defects. The Seven Tools method was applied as a quality control analysis instrument, including check sheets, histograms, scatter diagrams, stratification, Pareto charts, p-control charts, and fishbone diagrams. Based on data analysis, total production reached 4,369 units, with 870 defective products. The identified defect types included uneven stitching (47%), peeling paint (5%), stuck reclining mechanisms (20%), and poorly wrapped covers (26%). The main causes of defects were related to machine, human, method, and environmental factors. These findings provide a practical contribution by serving as a basis for evaluating and improving production processes through more effective quality control implementation and enhancing human resource performance to continuously reduce product defects.